Effect of the trans-Arctic invasion on Pliocene predator-prey interactions on Tjörnes Peninsula, Iceland - McCoy, Michelle; NC DOCKS at The University of North Carolina Wilmington (2009)
The significant impacts of some invasive species, such as the zebra mussel, have increased concerns about the long-term effects of invasive species. The fossil record provides a unique opportunity to track long-term changes caused by natural invasions. The Trans-Arctic Invasion (TAI) began after the Bering Strait opened at approximately 5.4-5.5 Ma, which enabled Pacific species to invade the Atlantic Ocean. Predatory naticid gastropods were among the invaders, allowing tracking of changes in naticid gastropod predation. To track the evolutionary integration of new species into the community, six samples postdating the invasion were collected from the Tjörnes beds of northeast Iceland, all from the Serripes zone (B14, U14, 15, B17, U17, B18; B=base, U=upper; bed number uses Bardarson's 1925 classification). For each sample, complete bivalve specimens (whether mold or shell) were identified to genus or species level, and drilling frequency (DF) and prey effectiveness (PE = incidence of failed drilling) were calculated for the assemblage and for selected taxa. Specimen length and height were measured, as was drill hole diameter. Thirteen bivalve genera, 6 of which were invasive, and 3 naticid species, 1 of which was invasive, were recognized in 1171 specimens. Drilling frequency decreased up-section for the assemblage (from 0.38 to 0.16) and two common prey taxa Macoma (invasive) and Thracia (native); drilling frequency did not change significantly for the native genera Arctica and Lentidium. Incomplete drill holes were found only in B14 (9 in Arctica and 1 in Thracia) and U14 (1 in Macoma). Drill hole location on the prey shell did not change up-section. Size selectivity, based on correlations of outer borehole diameter and prey length, was significant for Macoma and Arctica (complete drill holes) but not for Serripes, Lentidium, and Arctica (incomplete drill holes). Predators drilled relatively smaller prey up-section despite increases in average length of both Macoma and Thracia. The decreased drilling frequency ...